2000
DOI: 10.1155/mbd.2000.301
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical‐Experimental Study on the Structure and Activity of Certain Quinolones and the Interaction of Their Cu(II)‐Complexes on a DNA Model

Abstract: Theoretical electronic Structure methods have been employed to study the structure and activity of certain (free) quinolones and the interaction of their Cu(II)-complexes on a DNA model (Rhodamine 6G (rhod)). As a manner of assessing the generated geometries, the nalidixic acid geometrical parameters obtained were tested against the crystallographic ones and it was found that the average error in the calculated geometries is small. The present study allows us to (1) Rationalize the observed differences in anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 34 publications
0
15
0
3
Order By: Relevance
“…The mechanism of gatifloxacin action involves inhibition of bacterial DNA gyrase, which is essential for DNA replication, and it has been proposed that metal complex intermediates are involved in this process [3,4]. A study on the structure and activity of certain quinolones and the interaction of their Cu(II) complexes on a DNA model, suggested that the intercalation of the quinolone complexed to a metal is an important step in the mechanism of action of these drugs [5]. Number of studies confirmed that DNA-affinity of the quinolone, modulated by Mg (II), plays an important role in poisoning the cleavable gyrase-DNA complex and, consequently, in eliciting antibacterial activity by this family of drugs [6].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of gatifloxacin action involves inhibition of bacterial DNA gyrase, which is essential for DNA replication, and it has been proposed that metal complex intermediates are involved in this process [3,4]. A study on the structure and activity of certain quinolones and the interaction of their Cu(II) complexes on a DNA model, suggested that the intercalation of the quinolone complexed to a metal is an important step in the mechanism of action of these drugs [5]. Number of studies confirmed that DNA-affinity of the quinolone, modulated by Mg (II), plays an important role in poisoning the cleavable gyrase-DNA complex and, consequently, in eliciting antibacterial activity by this family of drugs [6].…”
Section: Introductionmentioning
confidence: 99%
“…Some evidence suggests that these drugs interact directly with DNA, blocking the activity of DNA-gyrase repair enzymes [2,3]. Recent studies indicate an important role of metal ions in the mechanism of action of these drugs; from investigations of the structure and activity of certain quinolones and the interaction of their Cu(II) complexes on a DNA model, it was suggested that the intercalation of the quinolone complexed to a metal is an important step in these processes [4]. In the last few years, we have described the structure and chemical behaviour of several complexes of cinoxacin (a classic quinolone) and ciprofloxacin as well as the antimicrobial activity of some of their compounds [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…From investigations of the structure and activity of certain quinolones and the interaction of their Cu(II) complexes on a DNA model, it was suggested that the intercalation of the quinolone complexed to a metal is an important step in their mechanisim of action. 3 Although reports indicate that the coordination of quinolones to metal ions such as Mg 2+ and Ca 2+ appears to be important for the activity of the quinolone antibiotics, 4 it has a detrimental effect on their absorption. 5 The interaction of metal ions with diverse deprotonated quinolones as ligands has been thoroughly studied.…”
Section: Introductionmentioning
confidence: 99%